DINAMIKA KEBIJAKAN ANTIKORUPSI DALAM ADMINISTRASI PEMERINTAHAN: ANALISIS TANTANGAN DAN PELUANG REFORMASI - Fanila Kasmita Kusuma (Media Bina Ilmiah, 2024)
Corruption remains one of the main obstacles to achieving clean, accountable, and effective public administration. Although Indonesia has adopted various anti-corruption policies through the establishment of independent agencies, the strengthening of legal frameworks, and the implementation of digital government technologies, significant challenges persist in their execution. This study aims to analyze the dynamics of anti-corruption policies in Indonesia’s public administration, focusing on the challenges of implementation and the potential reform opportunities that can be optimized. The research employs a qualitative approach through a literature review of laws and regulations, official institutional reports, and recent scholarly publications. The findings reveal that the dynamics of anti-corruption policy are influenced by legal-political factors, bureaucratic capacity, organizational culture, and coordination among law enforcement agencies. The identified challenges include political bargaining in policy-making, limited human resources, resistance to change, and weak internal oversight mechanisms. Conversely, reform opportunities lie in strengthening e-government, enhancing transparency and public participation, reforming civil service recruitment and promotion systems, and fostering cross-sector collaboration. In conclusion, the success of anti-corruption policies requires an integrated approach that combines technological innovation, institutional strengthening, and consistent political commitment to create a governance system free from corruption